PENGAMANAN PESAN TEXT DENGAN MENGGUNAKAN KRIPTOGRAFI KLASIK METODE SHIFT CHIPPER DAN METODE SUBSTITUTION CHIPPER - Fatkuroji, Moh; Widiyanto, Septian; Adnan, Govindo; Handoyo, Dwi Wahyu; Hasan, Mhd Arief (Riau Journal Of Computer Science, 2021)
Abstract - The very rapid advancement of telecommunication technology has provided many benefits. With this technology, long distance communication is not an obstacle. One technology that is always used is the sender of messages. At this time, the message application has been used by the community to convey messages to the recipient, the community uses the message application as a communication tool to send messages, the information provided is more precise and is a satisfaction in itself because using message sending application technology is more efficiently received to the recipient. Message content; constitute; security, social, education and professional and entertainment. In history, the Shift Chiper was used during ancient Rome, namely Julius Caesar. the technique used is very simple, namely by shifting each letter in its diplaintext. The main principle of the substitution cipher is to replace each letter on the plaintext into something. Substitution ciphers are incorporated into classical cryptographic algorithms. The idea is to replace one or more letters in plaintext with one or more letters in plaintext with certain rules. These rules are based on the encryption and decryption process. The substitution cipher has many variants or types.